The Moderating Role of Demographic Factors in the Relationship among Job Satisfaction, Work Environment, Work Motivation to Employee Performance - Hanafi, Kemal Muhammad; Syah, Tantri Yanuar Rahmat (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the effect of job satisfaction, work environment, and work motivation on employee performance and to determine the role of gender and duration as demographic factors that moderate the relationship between job satisfaction, work environment, work motivation, and employee performance. The object of this study is employees with staff positions working in telecommunications companies to PT. XL Axiata, PT. Indosat Ooredoo, and PT. Telekomunikasi Indonesia (Telkomsel) located in Jakarta. This study uses a quantitative approach which will use a questionnaire measuring tool. The total sample of this study was 590 respondents using a simple random sampling technique. To analyze the data used univariate cell means test and multiple linear regression test. The results of this study conclude that job satisfaction, work environment, and work motivation have a significant effect on employee performance. Demographic factors that become moderating have an influence on employee performance, but the exception for male gender is not better than women in job satisfaction, work environment, and work motivation on employee performance, while for work duration more than two years it is better than less than two years in the work environment and work motivation on employee performance, and are inversely related to job satisfaction.